PENGAYAAN 02-DARI UDARA DENGAN MEMBRAN POLIMER - Mulyati, Sri
ABSTRACT: Air separation by membrane to produce higher concentration of oxygen has been applied in industries. Oxygen enrich air is useful for welding process, combustion process and medical application. High permselective membrane is needed to produce high concentration of oxygen from air. Research is still being conducted in this field to develop a better membrane to this purpose. In this research influence of the membrane characteristic and structure is studied on the performance of air separation. Beside that the interaction between gas 02 and N2 in sorption and diffusion process is also considered. Quantitatively, the influenced of those factors can be described by determining transport parameters such as permeability coefficient (P), solubility coefficient (S). Diffusion coefficient (D) and separation factors (a). Laboratory experimental was done in three steps: i.e., (1) membrane preparation, (2) permeation of pure oxygen and nitrogen and (3) permeation of mixed gases (17 % 02 and 83 % N2). The types of membrane used are asymmetric dense polysulfone and cellulose acetate membranes and feed pressure was varied in the range of 5 to 15 bars. The mechanism of gas permeation through dense membrane was assumed to follow solution-diffusion mechanism. SEM (Scanning Electron Microscopy) obtains characterization of membrane structure and GC (Gas Chromatography) analysis for permeates composition. The experiment results show the solubility coefficient of both gases on cellulose acetate membrane are greater than those in polysulfone, it is expected that cellulose acetate possess greater polarity. In the other hand, diffusion coefficient of both gases in polysulfone are greater than those in polysulfone, due to the bigger repeating unit polysulfone has, which results in more free volume existed inside polysulfone membrane. The solubility coefficient of the two gases is relatively constant in the range of operating pressure, while the diffusion and permeability coefficient of the two gases increase by the increase of pressure. The separation process of mixed gases (17 % 02 and 83 % N2) result, oxygen concentration up to 26.02 %. The increase of the feed pressure increases the permeate flux, but decreases oxygen concentration slightly. The permeate flux is 0.0088 m-3l'rr .hr.